The Perspective of Gender and Islamic Law on Waithood Phenomenon in The Millennial Generation - Afrilian, Andre (Studi Multidisipliner: Jurnal Kajian Keislaman, 2024)
The recommendation to get married is clearly explained in the naṣ shara', but in reality at this time many teenagers who are considered mature and ready to get married are reluctant to get married and prefer to delay being single. This phenomenon has recently become widespread and is used as a principle by many teenagers in various parts of the world to Indonesia and is known as waithood. In the context of millennial adolescents today, the reasons that become factors for choosing waithood are so diverse that it is interesting to study and review their correlation with Islamic studies and gender issues. This research is a library research with a normative-sociological approach by analyzing the phenomenon of the idea of waithood through gender studies and Islamic law. The results of this study indicate that there are many factors, concepts and goals of waithood carried out by millennial adolescents today that contradict Islamic principles which clearly recommend getting married immediately if you are able and there is a connection to gender issues in the case of women who prefer waithood to not getting married, as well as gender inequality which is being called for by the UN program Transforming Our World: The 2030 Agenda for Sustainable Development which is not only on the issue of roles in marriage but even on many other factors so that the shift in the meaning of marriage and the decision to have children is no longer considered an obligation, but a choice that can be made by women